A Review of Research on The Impact of Differential Order Atmosphere - Li, Shitong (Transactions on Economics, Business and Management Research, 2024)
At present, research on the differential order atmosphere mainly focuses on its impact. The outcome variables mainly focus on behavior, and cognition and emotion are often used as mediating variables between perceived differential order atmosphere and employee work behavior. Scholars have not reached a consensus on whether the impact of a differential order atmosphere on employee behavior, cognition, and emotions is negative or positive. The research on the outcome variables of differential order atmosphere mainly focuses on three aspects: team and individual performance, employee silence and indifference behavior, and knowledge sharing and destruction. Some research on the differential order atmosphere currently only focuses on the consequences of its effects, without delving into the underlying mechanisms; Moreover, the impact of differential order atmosphere on employee behavior, cognition, and emotions is uncertain, and the effect of differential order atmosphere may have boundary conditions. Previous studies have explained this through organizational factors, leadership factors, and personal factors such as team trust, narcissistic leadership, regulatory orientation, and psychological resilience.